Some characteristics of sequences of iterations with random perturbations - Dorogovtsev, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For a sequence of random iterations, we study the set of partial limits and the frequency of visiting their neighborhoods.